hoe zit dat met die dy/du·du/dx

Je kunt (zoals in het boek) de kettingregel als volgt formuleren:

$
\Large\frac{{dy}}{{dx}} = \frac{{dy}}{{du}} \cdot \frac{{du}}{{dx}}
$

Voorbeeld

$y=\sqrt{3x-4}$ kun je opvatten als:
$y=\sqrt{u}$ met $u=3x-4$.

Dan is $
\Large \frac{{dy}}{{du}} = \frac{1}{{2\sqrt u }}
$ en $
\Large \frac{{du}}{{dx}}$=3, zodat:

$\Large\frac{{dy}}{{dx}}=\frac{{dy}}{{du}} \cdot \frac{{du}}{{dx}}$
$\Large\frac{{dy}}{{dx}}=\frac{1}{{2\sqrt u }} \cdot$ $3$
$\Large\frac{{dy}}{{dx}}=\frac{3}{{2\sqrt u }}$
$\Large\frac{{dy}}{{dx}}=\Large\frac{3}{{2\sqrt {3x - 4}}}$

©2004-2020 W.v.Ravenstein